Successful Treatment of Carbamazepine-Induced Toxic Epidermal Necrolysis With Clinical Gastrointestinal Involvement: A Case Report - Chi, Le Quynh; Anh, Nguyen Thi Van; Le, Nguyen Ngoc Quynh; Ha, Nguyen Thi Thu; Tien, Hoang Minh; Dien, Tran Minh (Frontiers in Pediatrics, 2022)
Background: Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) is a rare, life-threatening disease of the skin and mucosal surfaces. Although gastrointestinal manifestations in adults are potential prognostic factors for the disease severity, there are limited data on such cases and their standard management in the pediatric population. Case presentation: We herein report an 8-year-old girl case with a 1-year history of epilepsy, who presented bilateral conjunctivitis and progressively widespread bullous, pruritic eruption based on erythematous skin after administering carbamazepine. A diagnosis of carbamazepine-induced TEN was made, and the drug was immediately discontinued. The genetic screening result showed that the patient was positive for the HLA-B*15:02 allele. Then, her condition got worse by developing gastrointestinal involvement, including hematemesis and severely watery bloody diarrhea. Comprising of intravenous immunoglobulin and appropriate dose of systemic steroid raised a favorable outcome in this case. Multidisciplinary care of mucocutaneous involvement, supplemental nutrition, and fluid replacement was also critically warranted. This report aims to contribute to the current literature on TEN-related gastrointestinal manifestations in pediatrics and highlight the need for further investigations in determining the optimal treatment in such cases. Conclusion: In conclusion, we have reported successful treatment of the TEN-related gastrointestinal manifestations in pediatrics, which should be critically considered in patients with SJS/TEN. Since it may significantly contribute to the illness's poor prognosis, further investigations in determining the standard management in such cases are necessary.